Emulsion Waterproof Agent and Its Effects on Intrinsic Properties of Gypsum - Pan, Hong; Li, Guozhong (Asian Journal of Chemistry, 2013)
A core-shell structural emulsion waterproof agent containing fluorine and silicone was prepared by gradual emulsion polymerization and its structure and properties were analyzed by fourier transform infrared spectrophotometer, integral-rotation contact angle measuring device and X-ray photoelectron spectrometer. Then the waterproof agent was added into gypsum slurry. Its modification effects on the 2 and 24 h water absorption and 24 h flexural, compressive softening coefficient of gypsum were studied and the action mechanisms were investigated. The research indicates that the fluorine and silicone monomers were effectively introduced into the molecular structure of the waterproof agent during the process of synthesis, which gave the latex film excellent hydrophobicity. When the dosage of waterproof agent reached to 9 %, the water-resistance of gypsum sample was improved significantly compared with the blank sample.